ANALISA KINERJA TERHADAP WAKTU DAN BIAYA DENGAN METODE EARNED VALUE ANALYSIS PADA PEMBANGUNAN GEDUNG AUDITORIUM IAIN SAMARINDA - FEBRIANI, NOR FAJRI (KURVA S JURNAL MAHASISWA, 2018)
Planning, cost control, and time are part of the overall construction project management. In addition, quality, projects can also be known in terms of cost and time. The danger of deviations from plans in terms of costs and time that are very important for construction construction must be measured continuously. Significant cost and time deviation. Poor depreciation. As for the Performance Analysis of Time and Cost with Earned Value Analysis Method at the Construction of the IAIN Samarinda Auditorium Building using Earned Value Analysis Method by collecting data in the field at the IAIN Auditorium Building Construction Project in Samarinda. In this study the Performance Analysis of Time and Cost with Earned Value Analysis Method in the Construction of the IAIN Samarinda Auditorium Building results in the SPI value of 0.853 while the CPI is 1.006, which means that the project experiences delays in terms of schedule but issues less actual costs of work already done. For the ETC value of Rp. 13,380,535,283 and an EAC value of Rp. 30,483,085,771 while the ECD value to 294 days for project completion time is recommended so that the relevant parties control the progress of the performance in the following weeks and find a solution so that the project is completed on time with the remaining costs.